Green Intellectual Capital and Environmental Management Accounting : How Does It Influence Environmental Performance ? - Az'mi, Yanis Ulul; Kristina, Gabriela Rachel (Indonesian Journal of Economics, Social, and Humanities, 2024)
Environmental Management Accounting (EMA) supports environmental and green resources management strategies. EMA can facilitate environmental actions from organizations or companies to create superior performance by aligning actions or behavior with the goals and values the organization or company wants to achieve. By aligning environmental resources and using an appropriate management accounting system, it is hoped to facilitate the management of green resources and support the achievement of strategic goals, resulting in increased sustainability performance. The hypothesis in this theoretical model is that the Environmental Management Accounting mechanism can help businesses coordinate, measure, and manage better, namely displaying GIC elements, green human capital, green structural capital, and green relational capital, which can improve Environmental Performance. Consequently, this study is inspired by resource orchestration theory and presents a new approach, natural resource orchestration. The purpose of this study to investigate how business rely on EMA to interpret GIC into Environmental Performance. A sample of forty firms was obtained, based on the data collected from the Annual Reports and Sustainability Reports of companies registered on the Indonesia Stock Exchange (BEI) and following PROPER working in the energy industry. The Statistical Package for the Social Sciences (SPSS version 20) was used to test the model theoretically and used path analysis. These results bolster the idea that EMA mediates the relationship between GIC and environmental performance.